DETECTION OF KPC GENE IN ANTIBIOTIC RESISTANT KLEBSIELLAPNEUMONIA CAUSING URINARY TRACT INFECTION - JIHAD MOHAMMED ABDULHASAN, (International Journal of Pharma and Bio Sciences, 2014)
Klebsiella pneumonia carbapenemases (KPCs) are class A variant of β –lactamase enzymes capable of hydrolyzing all known β –lactam antibiotics. Worldwide spread of KPC producing strain makes them a potential threat for current antibiotic based therapy. In this study, we isolated the K. pneumoniae from the urine samples and screened for antibiotic resistance. Then molecular amplification techniques PCR was used for identification of KPC gene in these isolated samples. The PCR results coordinate with the antibiotic susceptibility testing and KPC positive isolates showed a multidrug resistant.Considering the potential for rapid horizontal and vertical transmission of KPC genes, prompt recognition is critical. This study validated a rapid, sensitive, and specific PCR assay for the detection of KPC gene.